2020
DOI: 10.1002/ece3.7052
|View full text |Cite
|
Sign up to set email alerts
|

Environment‐induced changes in reproductive strategies and their transgenerational effects in the three‐spined stickleback

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…Indeed, in a recent study, we found that the level of oxidative DNA damage in sperm negatively influenced egg fertilization success in the same study population (our unpublished data). It is interesting to note that juveniles from redder families tend to die younger in this population due to genetic conflict between attractiveness and viability [ 36 ], and females do not prefer redder males in another adjacent annual population [ 57 ]. Nevertheless, red colouration may be selected due to its benefits for male sticklebacks in territory defence against other males [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in a recent study, we found that the level of oxidative DNA damage in sperm negatively influenced egg fertilization success in the same study population (our unpublished data). It is interesting to note that juveniles from redder families tend to die younger in this population due to genetic conflict between attractiveness and viability [ 36 ], and females do not prefer redder males in another adjacent annual population [ 57 ]. Nevertheless, red colouration may be selected due to its benefits for male sticklebacks in territory defence against other males [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this annual population, fish go through a single long reproductive season during which females spawn on average six clutches [ 72 ], and successful males simultaneously take care of multiple clutches from different females in their nests [ 73 ]. Thus, males’ behaviours during courtship, which are related to their cognitive ability [ 57 ] and possibly to their parental care behaviour, may be under strong sexual selection in this population. Contrary to expectations, in these annual populations, sexual ornaments of males may not honestly signal their physiological and physical state because they invest at maximum in the single reproductive season due to their relatively low life expectancy compared to northern populations [ 13 , 74 ].…”
Section: Discussionmentioning
confidence: 99%